THE RELATIONSHIP BETWEEN SMARTPHONE USE AND EARLY CHILDHOOD BEHAVIOR AT TK NEGERI PEMBINA SUMEDANG - Zaenurdin; Diding Kelana Setiadi; Emi Lindayani (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
In the current era, it is not only teenagers or adults who use smartphones, but even young children or preschoolers have become adept at using them. In Indonesia, more than 50% of smartphone users are under 25 years old. Adults over 25 years old account for 32%, and teenagers aged 12 to 21 years account for 25%. The percentage of children using smartphones at the age of 5 was 38% in 2011, increased to 72% in 2013, and further rose to 80% in 2015. The purpose of this study is to determine the relationship between smartphone use and the behavior of young children at TK Negeri Pembina Sumedang. This research employs a quantitative correlation method with a survey approach. The population in this study were 145 children, the sample used was 59 respondents calculated using cluster random sampling technique. The results show a significant relationship between smartphone use and the behavior of young children, as indicated by a chi-square test result with a P-value of 0.000. Specifically, children who use smartphones more frequently tend to have irregular eating patterns, poorer sleep quality, and difficulty focusing on learning compared to children who use smartphones less often. The conclusion of this study is that there is evidence of a relationship between smartphone use and eating patterns, sleep quality, and learning behavior in young children at the kindergarten, supported by the study’s findings. The recommendation of this study is that efforts are needed to monitor children’s smartphone use to prevent negative impacts on their behavior in the future.